Unity in Diversity: The Christian Model of Unity - Pathil, Kuncheria (1987)
According to Alfred Loisy, the French Catholic Modernist theologian, Jesus preached the coming of the Kingdom of God, but what came into existence was the Church. Loisy questioned the absolute and unchangable character of the Church, its structures and dogmas, and argued that every- thing in the Church must give way to the Kingdom of God. There seems to be some truth in his statement. The Jesus' Movement which was meant to be the harbinger and servant of the Kingdom of God, became in the course of history one among the many religions in whose name wars and crusades were waged, people were converted by force, conscientious objectors were persecuted and burned at the stake, and walls separating man from man were erected. Not only that, Christianity itself became gradually divided into various Churches, denominations and sects followed by mutual condemna- tions and excommunications. All the same, Christianity claims to be the sign or sacrament and instrument of the unity of all humankind: "By her relationship with Christ, the Church is a kind of sacrament or sign of inti- mate union with God, and of the unity of all mankind.! Does this not amount to a contradiction and a grossly false' statement? Has the Church's claim to be a force and instrument of unity any credibility? In the following pages we shall investigate the Church's original vision and practice of unity. the forces which brought about the historical divisions in the Church and the present search of the Churches, for a model of unity.
Keywords: Christianity; Unity in Diversity